1 개요[ | ]
- binomial theorem
- 이항정리
- 두 항의 합의 거듭제곱을 전개하는 방법에 관한 정리
- [math]\displaystyle{ (x+y)^n }[/math][math]\displaystyle{ =_nC_0x^ny^0+_nC_1x^{n-1}y^1+_nC_2x^{n-2}y^2+\cdots+_nC_{n-1}x^1y^{n-1}+_nC_nx^0y^n }[/math]
2 예시[ | ]
- [math]\displaystyle{ (x+y)^1 = x + y }[/math]
- [math]\displaystyle{ (x+y)^2 = x^2 + 2xy + y^2 }[/math]
- [math]\displaystyle{ (x+y)^3 = x^3 + 3x^2y + 3xy^2 + y^3 }[/math]
- [math]\displaystyle{ (x+y)^4 = x^4 + 4x^3y + 6x^2y^2 + 4xy^3 + y^4 }[/math]
- [math]\displaystyle{ (x+y)^5 = x^5 + 5x^4y + 10x^3y^2 + 10x^2y^3 + 5xy^4 + y^5 }[/math]
3 같이 보기[ | ]
4 참고[ | ]
편집자 Jmnote Jmnote bot
로그인하시면 댓글을 쓸 수 있습니다.